Investigation of the body composition and maximal oxygen consumption capacity of elite boxing and wrestling athletes - Balci, A.; Tortu, E.; Kabak, B.; Akinoglu, B.; Hasanoglu, A.; Kocahan, T. (Turkish Journal of Sport and Exercise, 2020)
The aim of the study is to compare body composition and maximal oxygen consumption of elite boxing and wrestling athletes and to investigate the relationship between body composition and maximal oxygen consumption. A total of 26 elite athletes (13 boxing and 13 wrestling) were included in the study. On the same day, the and body composition assessment and maximal oxygen consumption measurement of the athletes were performed. Body composition evaluation of athletes was made with MF-BIA (Tanita MC-980, 1000 kHz, Tokyo, Japan) device. Maximal oxygen consumption measurement was made using a direct method breath-by-breath automatic portable gas analysis system (Cosmed K5, Italy). Mann Whitney U Test and Spearman Correlation Test were used for statistical analysis. The statistical significance level was determined as p <0.05. There was not any difference in body weight, body fat percentage, and relative oxygen consumption values of boxing and wrestling athletes (p> 0.05); however, there were statistically significant differences in the Body Mass Index, muscle mass, absolute oxygen consumption, carbon dioxide production, respiratory coefficient, and heart rate values (p <0.05). In boxing and wrestling athletes, there was a strong negative correlation between BMI and body fat percentage and relative oxygen consumption values (p <0.05); Muscle mass and relative oxygen consumption values were found to be strong in boxing athletes and moderate in wrestling athletes (p <0.05). As a result of our study, it has been observed that there is a relationship between body composition and maximal oxygen consumption of both boxing and wrestling athletes. In addition, with the knowledge that body composition is important in strength and anaerobic power-based sports branches, it raises the idea that athletes in these branches should do aerobic exercises to keep their body composition at the targeted levels.